HUBUNGAN WAHYU DAN AKAL DALAM TRADISI FILSAFAT ISLAM - Mukhtasar Syamsuddin (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2012)
This paper attempts to represent the world of philosophical thinking on the relationship between faith and reason among moslem scholars and Islamic doctrines. Qoran is the fundamental principle in inspiring any attempt of reason to find the truth. It means that reason still has its place and possibility to find the truth based on the truth of faith which is inspired by Qoran. It is the focus of discussion between the two outstanding moslem scholars, Ibnu Rusyd (520 H/ 1126 A-595/ 1198) and Ibnu Taimiyyah (662/ 1263). Ibnu Rusyd approaches the correlation between faith and reason in the term of relationship (ittisal). Meanwhile, Ibnu Taimiyyah explores the correlation between faith and reason under the term of muwafaqat. These two scholars are different with one another especially in exploring the fundamental meaning of reason (’aql) and revelation (al-naql).